Land Use Systems, Soil Texture, Control Carbon and Nitrogen Storages in the Forest Soil of UB Forest, Indonesia - Kurniawan, Syahrul; Utami, Sri Rahayu; Mukharomah, Miftakhul; Navarette, Ian A.; Prasetya, Budi (Faculty of Agriculture University of Brawijaya in collaboration with PERAGI, 2019)
Differences in land use systems may resulted in different soil cover, litter input, and soil management practices, and consequently affect to soil nutrient stock. The study aimed to assess soil carbon (C) and nitrogen (N) storages on various soil depths from difference land use systems within UB forest. The research was conducted in UB forest, Malang – Indonesia, from April to November 2017. Soil sample was collected from four soil depths (0-0.1, 0.1-0.3, 0.3-0.5, and 0.5-1.0 m) within five land use systems, including (1) protected area; (2) pine + coffee; (3) pine + crops; (4) mahogany + coffee and (5) mahogany + crops, each with three replicate plots. Soil C and N concentrations, soil texture, and bulk density, were measured. The study showed significant difference in soil C and N storages among land use systems. In 0.5 m depth of soil, soil C and N storages was higher in protected area (64% and 53%, respectively) as compared to other land use systems. The result support clay content controls soil C and N stock, whereas vegetation determines soil N stocks. Therefore, proper management in vegetation and soil were needed to conserve soil C and N storages.